Pengaruh Servant Leadership Terhadap Employee Loyalty di Rocky Plaza Hotel Padang - Haadi Razzak Ramadhan; Arif Adrian (Departemen Pariwisata Universitas Negeri Padang, 2024)
This research aims to investigate the influence of servant leadership on employee loyalty at Rocky Plaza Hotel Padang. Identified issues include a high employee turnover rate, low communication skills, lack of leadership attention to employee work-life balance, and oe employee loyalty. The research objectives include a description of servant leadership and employee loyalty. This study is expected to provide theoretical contributions for hotel management, employee, future researchers, and the author. The tourism sector in Padang City, especially at Rocku Plaza Hotel, is experiencing growth. However, employee turnover rates remain high, and employee loyalty needs improvement. Servant leadership is considere a leadership style that can enhance employee loyalty. Companies need to a pay attention to factor affecting employee loyalty to create a better working environment. The research method used is causal associative with a quantitative approach through surveys. The research population consists of all employees at Rocky Plaza Hotel Padang, with sampels selected using purposive sampling techniques. Data were collected through questionnaires with a Likert scale to measure the variables of servant leadership and employee loyalty. This study was conducted to evaluate the relationship between servant leadership and employee loyalty at Rocky Plaza Hotel Padang. A total 96 respondents, with the majority aged 26-30 years and having worked at the hotel for 2-5 years, were surveyed. Data analysis revead a positive and significant influence between servant leadership and employee loyalty.